2012
DOI: 10.1038/oby.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Environmental School‐Based Obesity Prevention Program on Changes in Body Fat and Body Weight: A Randomized Trial

Abstract: This study tested the efficacy of two school-based programs for prevention of body weight/fat gain in comparison to a control group, in all participants and in overweight children. The Louisiana (LA) Health study utilized a longitudinal, cluster randomized 3-arm controlled design, with 28 months of follow-up. Children (N=2060; M age = 10.5 years, SD = 1.2) from rural communities in Grades 4 to 6 participated in the study. 17 school clusters (M = 123 children/cluster) were randomly assigned to one of three prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(144 citation statements)
references
References 37 publications
6
131
0
7
Order By: Relevance
“…For example, the effect of interventions or second servings on the food intake of elementary school children in school cafeterias has been demonstrated in a number of studies that relied on the Digital Photography of Foods Method (Martin et al, 2007, Williamson et al, 2012, Williamson et al, 2007) and the method has been used to quantify the food intake behavior of preschool-age children in HS and their homes (Nicklas et al, submitted for publication-b). Further, this method has been used to objectively determine if food provision and intake in school cafeterias (Martin et al, 2010) and HS Centers (Nicklas et al, submitted for publication-a) meets national guidelines, and this information can be used to inform policy decisions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effect of interventions or second servings on the food intake of elementary school children in school cafeterias has been demonstrated in a number of studies that relied on the Digital Photography of Foods Method (Martin et al, 2007, Williamson et al, 2012, Williamson et al, 2007) and the method has been used to quantify the food intake behavior of preschool-age children in HS and their homes (Nicklas et al, submitted for publication-b). Further, this method has been used to objectively determine if food provision and intake in school cafeterias (Martin et al, 2010) and HS Centers (Nicklas et al, submitted for publication-a) meets national guidelines, and this information can be used to inform policy decisions.…”
Section: Discussionmentioning
confidence: 99%
“…While intraindividual factors, including beliefs, knowledge, and skills, are important aspects in the behaviour change process, interventions which are limited to targeting change at an individual level fail to address the importance of broader social, physical, economic and political contexts. The breakdown of study types by social ecological level was shown to be pyramid-shaped with the vast majority of studies focused on the individual [22, 2427, 33, 34, 3645, 48, 49] and a few interventions that included components which spanned into the interpersonal [23, 28, 30, 31, 35, 46, 47] or organizational realms [21, 29, 50]. Within organizational realms, interventions tended to target making nutritional or physical activity resources available.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a school setting, playgrounds and school yards were made accessible for children to play after end of curricular program, and school canteens were obliged to have fresh fruit and freshly made juices [32]. Another study program modified the cafeteria food service program (the contents of vending machines), and physical education programs [50] and another intervention included implementing short PA breaks during lessons [21]. …”
Section: Discussionmentioning
confidence: 99%
“…It was unclear whether the relationships seen in this age group would apply to older children. However, a recent follow-up re-evaluating outcomes when the children were in fifth grade identified a “relatively small” effect on body fat effect and only in boys 97,99-101 . Given the known decrease in body fat that occurs in boys with proximity to puberty an effect of PE on obesity is difficult to decipher.…”
Section: Introductionmentioning
confidence: 99%